A tabuada em diferentes tempos pedagógicos: do ensino ativo para a escola ativa - Rodrigues, Dirce Lurdes Pires [UNIFESP] (2015)
The dissertation "The arithmetic table in different educational stages: from active teaching to active school," analyses the transformation of arithmetic tables, as didactic and pedagogical instrument, during the post-republic educational renovations. The work is written from an historical point of view, and the cultural history is the methodological approach. Within the historical perspective, the research of the sources considers the educational periodicals inserted into the digital repository of Santa Catarina, in the History of Mathematics Education area, one of the research projects of History of Mathematics Education Group in Brazil. From the empiricism of the secular school to the systematization of teaching in which the psychology emerges to give subsidies to education, the narrative of the arithmetic table trajectory permits, first of all, that educators think the arithmetic table sometimes as an isolated understanding and its peculiarities, and sometimes as a component of a school culture transformation within each temporality, agent / instrument, a variety of methods and procedures operating in all the basic knowledge of learning, in particular in arithmetic.